(3HTGQI GdbOjS GdLdjd dhbG GdQShds
(3ChdgG (B:s
(3deG cGf cKjQhf bOeG QShG oeTJedoG Ydi GdCTjGA GdoeJMbbI ajfG s
(3BNQgG (B:s
(3hYGOh Edi ChQTdje HaQM YXje hcGfhG aj Gdgjcd cd hbJ jSLhf hjHGQchf Gddg Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcJH GdSeGhjIs